Antisipasi, Rujukan dan Fokus Pengaturan Sebagai Prediktor Perilaku Sehat - Lubis, Dharmayati Utoyo; Takwin, Bagus; Panggabean, Sahat Krisfianus (Makara Human Behavior Studies in Asia, 2011)
The aim of this study was to understand the relation between principles of self-regulation and health behaviors, including which self-regulation principles used. Using three principles of self-regulation which are regulatory anticipation, regulatory reference, and regulatory focus (Higgins, Grant, & Shah, 1999) this study examined the role of those principles on health behavior among people in DKI Jakarta. The health behavior was divided into health promotive behavior and health preventive behavior. This study was conducted to 385 citizens of DKI Jakarta (200 males and 185 females with average age is 32 years old). Data analysis using multiple regressions indicated the role of self-regulation principles on health behaviour.